2009
DOI: 10.1029/2009gl039525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultra‐low‐frequency waves at Mercury under northward and southward IMF

Abstract: [1] Narrow-band ultra-low-frequency (ULF) waves at frequencies greater than the He + cyclotron frequency (f cHe+ ) were detected during MESSENGER's first two Mercury flybys. The waves were observed primarily between closest approach (CA) and the outbound magnetopause. The magnetosphere was very quiet during the first flyby (M1) and highly disturbed during the second flyby (M2); that ULF waves were observed during both flybys despite these different magnetospheric conditions is remarkable. The wave frequency st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The total wave power also had a maximum near the equator, suggesting that there may be an equatorial source for these waves. Most of the waves observed by Boardsen et al [] had a near‐linear polarization, where the handedness was most often RH (right handed), as previously observed by Boardsen et al [, ]. Kim and Lee [] predicted that a RH polarized compressional mode would undergo a mode conversion where local gyroresonance is met, such that the energy would be transferred to a LH (left‐handed) polarized mode such as an ion‐cyclotron wave (ICW).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The total wave power also had a maximum near the equator, suggesting that there may be an equatorial source for these waves. Most of the waves observed by Boardsen et al [] had a near‐linear polarization, where the handedness was most often RH (right handed), as previously observed by Boardsen et al [, ]. Kim and Lee [] predicted that a RH polarized compressional mode would undergo a mode conversion where local gyroresonance is met, such that the energy would be transferred to a LH (left‐handed) polarized mode such as an ion‐cyclotron wave (ICW).…”
Section: Introductionmentioning
confidence: 83%
“…More recent observations at Mercury have demonstrated that it is indeed common to find wave activity with frequencies close to, but not exactly equal to, the proton gyrofrequency, f cH+ [e.g., Boardsen et al , , ; Echer , ; Anderson et al , ; Boardsen et al , ], where the local proton gyrofrequency is typically in the range of 1 < f cH+ <2 Hz. Boardsen et al [] found that these waves were often accompanied by harmonics and that the most common peaks in wave power occurred in three places: a dominant peak just below f cH+ , a second peak close to 2 f cH+ , and just below f cHe++ .…”
Section: Introductionmentioning
confidence: 99%
“…Narrowband harmonic waves, whose fundamental is near the proton cyclotron frequency ( f cp ) at the magnetic equator, are frequently observed in Mercury's inner (<2 Mercury radii ( R M ), 1 R M ~2440 km) magnetosphere [ Russel , ; Boardsen et al , , , ]. The statistics of these waves are summarized in Figures 7, 8, and 9 of Boardsen et al [].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that only low-latitude flybys have observed ULF waves, and the high latitude Marinter-10 flyby did not seen it. It has been considered that these waves might be confined to the Mercury's magnetic equator (e.g., Boardsen et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%